Gender differences in mortality among ST elevation myocardial infarction patients in Malaysia from 2006 to 2013 - Juhan, Nurliyana; Zubairi, Yong Zulina; Zuhdi, Ahmad Syadi Mahmood; Khalid, Zarina Mohd; Ahmad, Wan Azman Wan (King Faisal Specialist Hospital & Research Centre, 2018)
BACKGROUND: Coronary artery disease (CAD) is one of the leading causes of death in Malaysia. However, the prevalence of CAD in males is higher than in females and mortality rates are also different between the two genders. This suggest that risk factors associated with mortality between males and females are different, so we compared the clinical characteristics and outcome between male and female STEMI patients.